Dense nanostructured calcium phosphate coating on titanium by cold spray. Issue 4 (April 2017) - Vilardell, A.M.; Cinca, N.; Cano, I.G.; Concustell, A.; Dosta, S.; Guilemany, J.M.; Estradé, S.; Ruiz-Caridad, A.; Peiró, F.
Abstract: This article deals with the understanding of building-up mechanisms of bioactive nanocrystalline hydroxyapatite coatings by Cold Spray, revealing very promising results in contrast to more conventional techniques such as Plasma Spray. A full characterization of feedstock and coatings is provided. The agglomerated structure of the powder proved to be suitable to obtain successfully thick hydroxyapatite coatings. A crystallite size below ∼20 nm in the powder and the as-sprayed coatings is calculated by the Rietveld X-ray refinement method and agreed by Transmission Electron Microscopy. Some wipe tests were carried out on Ti6Al4V substrates in order to study the deposition of single particles and the nanoscale features were evaluated. The resulting structure indicates that there is no delimitation of particle boundaries and the overall coating has been formed by effective compaction of the original nanocrystallites, leading to consistent and consolidated layers.